NARINGIN AMELIORATES RENAL IMPAIRMENT ON CYCLOSPORINE (A)-INDUCED NEPHROTOXICITY IN RATS: INVOLVEMENT OF iNOS - YAMINI CHANDRAMOHAN; CHETENCHERY SOMASUNDARAM PARAMESWARI (International Journal of Pharma and Bio Sciences, 2013)
The therapeutic effecicacy of a flavonoid Naringin (NG) against Cyclosporine A (CsA) induced nephrotoxicity was investigated in this study. Nephrotoxicity was induced in male albino wistar rats by injecting 25mg/kg body weight of CsA for a period of 21 days. CsA induced rats were also cotreated with 40mg of Naringin (NG/kg body weight) orally. After the experimental period the serum levels of urea, uric acid and creatinine were found to be elevated, followed by the decrease in creatinine clearance, whereas the levels of ALP, ACP were increased in serum of CsA induced rats. A significant decrease in LDH levels were observed in CsA induced animals compared to control. Immunohistochemical staining of inducible nitric oxide synthase (iNOS) expression was studied and NG co treatment significantly decreased the expression of iNOS in CsA challenged rats. This data was further evidenced by western blotting expression pattern of iNOS in experimental rats.